(untitled) (Journal of Geography and Environmental Management, 2019)
A study was conducted to determine of the norm of spring flow of the unexplored rivers of the Esil and Nura-Sarysu basins of Central Kazakhstan. In the absence of observational data on the characteristics of the spring runoff, the norm of the runoff layer and the maximum runoff of the spring flood, a method of studying the relationship between the annual runoff and the physical geographic factors forming the spring runoff of the lowland rivers was applied. In the work, the determination of the norm of the spring runoff of the Esil and Nura - Sarysu basins was made according to the regional dependencies of the annual flow on the determining factors. At the beginning, the dependences of the norm of the spring runoff layer on the catchment area were investigated. Four dependencies were obtained: for the Basins Esil River, the Selety River and the Karasu River separately, and also for the entire basin of the Water economic Esil river. It is recommended to determine the spring runoff layer by separate river basins. In all cases, feedback is obtained h = f (F), i.e. the runoff layer decreases with increasing catchment area. It was shown that for an approximate assessment of the spring flow rate and maximum flow module of unstudied rivers of Central Kazakhstan, dependencies of the spring flow layer on the catchment area and dependence of the maximum flow module on the catchment area of the study area can be used.